Impact of Alexithymia on the Lipid Profile in Major Depressed Individuals. (16th June 2022) - Point, Camille; Wacquier, Benjamin; Dosogne, Marjorie; Al Faker, Mohammed; Willame, Hadrien; Loas, Gwenolé; Hein, Matthieu
Abstract : Background . The cooccurrence of major depression and dyslipidaemia is associated with negative cardiovascular outcome, which seems to justify a better identification of the factors favouring the development of dyslipidaemia in major depressed individuals. In the literature, there are arguments in favour of a special relationship between dyslipidaemia and alexithymia. However, despite a high prevalence of alexithymia in major depressed individuals, no study has investigated the impact of this personality trait on the lipid profile in this particular subpopulation. Given these elements, the aim of this study was therefore to investigate the risk of dyslipidaemia associated with alexithymia in major depressed individuals to allow better cardiovascular prevention in this subpopulation. Subjects and Methods . Demographic and polysomnographic data from 242 major depressed individuals recruited from the clinical database of the sleep laboratory were analysed. Only individuals with a diagnosis of dyslipidaemia according to the diagnostic criteria of the International Diabetes Federation at admission were included in the "dyslipidaemia" group. Logistic regression analyses were used to determine the risk of dyslipidaemia associated with alexithymia in major depressed individuals. Results . The prevalence of dyslipidaemia was 43.8% in our sample of major depressed individuals. After adjusting for the main confounding factors, multivariate logistic regression analyses demonstrated that alexithymia was a risk factor for dyslipidaemia in major depressed individuals. Conclusions . In this study, we found that alexithymia is a risk factor for dyslipidaemia in major depressed individuals, which seems to justify better identification and adequate management of this personality trait in order to allow a better lipid profile in this subpopulation at high cardiovascular risk.